Serotonin‐deficient neonatal mice are not protected against the development of experimental bronchopulmonary dysplasia or pulmonary hypertension. Issue 19 (6th October 2022) - Roberts, Danielle S.; Sherlock, Laura G.; Posey, Janelle N.; Archambault, Jamie L.; Nozik, Eva S.; Delaney, Cassidy A.
Abstract: Serotonin (5‐hydroxytryptamine, 5‐HT) is a potent pulmonary vasoconstrictor and contributes to high pulmonary vascular resistance in the developing ovine lung. In experimental pulmonary hypertension (PH), pulmonary expression of tryptophan hydroxylase‐1 (TPH1), the rate limiting enzyme in 5‐HT synthesis, and plasma 5‐HT are increased. 5‐HT blockade increases pulmonary blood flow and prevents pulmonary vascular remodeling and PH in neonatal models of PH with bronchopulmonary dysplasia (BPD). We hypothesized that neonatal tph1 knock‐out (KO) mice would be protected from hypoxia‐induced alveolar simplification, decreased vessel density, and PH. Newborn wild‐type (WT) and tph1 KO mice were exposed to normoxia or hypoxia for 2 weeks. Normoxic WT and KO mice exhibited similar alveolar development, pulmonary vascular density, right ventricular systolic pressures (RVSPs), and right heart size. Circulating (plasma and platelet) 5‐HT decreased in both hypoxia‐exposed WT and KO mice. Tph1 KO mice were not protected from hypoxia‐induced alveolar simplification, decreased pulmonary vascular density, or right ventricular hypertrophy, but displayed attenuation to hypoxia‐induced RVSP elevation compared with WT mice. Tph1 KO neonatal mice are not protected against hypoxia‐induced alveolar simplification, reduction in pulmonary vessel density, or RVH. While genetic and pharmacologic inhibition of tph1 has protective effects in adult models of PH, our results suggest that tph1 inhibition would not be beneficial in neonates with PH associated with BPD. Abstract : Serotonin‐deficient neonatal mice are not protected against hypoxia‐induced alveolar simplification, reduction in pulmonary vessel density, or RVH. While genetic and pharmacologic inhibition of tryptophan hydroxylase 1 (TPH1) has protective effects in adult models of pulmonary hypertension (PH), our results suggest that tph1 inhibition would not be beneficial in neonates with PH associated with BPD.